Regarding the effect of zone C earth excavation on reinforcement approach - BUCG-ABC Joint Venture (BUCG-ABC JV) (2023)
This record consists of general correspondence regarding the effect of zone C earth excavation on reinforcement approach for BRACU new campus project construction.